Development and Optimization of Network Music Course Resources Based on Data Mining Technology under the Personalized Online Education Environment. (26th September 2022) - Yan, Xiuli
Abstract : The ever-evolving Internet technology has brought more information resources for music teaching than ever before. For music educators, figuring out how to create and use these tools more effectively has become a pressing concern. China will usher in a new age of innovation and integration between the Internet and different traditional businesses with the idea of "Internet Plus." MOOCs present significant challenges to traditional teachers and teaching methods as a typical practice of the transformation of education informatization to innovation, and they also drive global education toward a new process of informatization development. This paper adopts Internet thinking as the guiding ideology for the development of future music education concepts and, concurrently, conducts specific transformation research based on Internet technology from four aspects: music teaching content, music teaching methods, music education concepts, and the passing down of traditional music culture. The improved association rule algorithm is used to organise the students' access data, decide which high-frequency websites are accessible to the students, and realize the intuitive positioning of high-frequency access and learning issues. Assist the school's decision-making and educational levels in identifying the issues that students have with their learning, and then, improve the network teaching platform's material to complete the task of personalized network education.